Comparison of the total phenolic and flavonoid contents of Amomum compactum Sol. Ex Maton from districts Linggo Asri and Paninggaran, Pekalongan Regency - Mahfur Mahfur; Kharismatul Khasanah; Metha Anung Anindhita; Safira Galuh Chandra; Alfiana Nur Hidayah (Sasambo Journal of Pharmacy, 2023)
Cardamom (Amomum compactum Sol. Ex Maton) is one of the largest contribution in biopharmaceutical production plants in Indonesia that is equal to 12.22% and yield reaching 105.735 kg/year in Pekalongan Regency. The largest cardamom production in Pekalongan Regency is in 2 districts, namely Linggo Asri and Paninggaran. Cardamom is used in traditional medicines, because it has chemical compounds such as flavonoids and phenolics. The aim of this study was to compare total flavonoids and total phenolics content in Amomum compactum Sol. Ex Maton extract originates from Linggo Asri and Paninggaran district, Pekalongan Regency. The samples were extracted by water extraction, and then phytochemical contents were identified with HCl and FeCl3 reagent. The samples were calculated of total flavonoids and total phenolics content by spectrometric using aluminum chloride colorimetric assay and Folin–Ciocalteu method. The result showed a significant difference in the levels of total phenolic content between Amomum compactum Sol. Ex Maton extract origin from Linggo Asri district 41.43±0.54 µg/mg and Paninggaran district 120.55±1.89 µg/mg, but it was not found in total flavonoid content where from Linggo Asri district 289.06±4.1 µg/mg and Paninggaran district 303.81±0.5 µg/mg. The conclusion is Amomum compactum Sol. Ex Maton extract originates from Linggo Asri and Paninggaran district of Pekalongan city showed a significant difference in the levels of total phenolic content, but it was not found in total flavonoid content.